2016
DOI: 10.1016/j.envint.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Governance and networks for health co-benefits of climate change mitigation: Lessons from two Indian cities

Abstract: Health has been the main driver for many urban environmental interventions, particularly in cases of significant health problems linked to poor urban environmental conditions. This paper examines empirically the links between climate change mitigation and health in urban areas, when health is the main driver for improvements. The paper aims to understand how systems of urban governance can enable or prevent the creation of health outcomes via continuous improvements in the environmental conditions in a city. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…An India‐wide study suggested that an increase in electricity consumption, modern cooking and clean water could lower short‐term morbidity for 2.4 million people with only modest increases to GHG emissions (Ahmad, Pachauri, & Creutzig, ). A range of studies point out that public and para transport can enhance safety, health and GHG mitigation (Ahmad et al, ; Arora et al, ; Doll & Balaban, ; Guttikunda, ; Maitra & Sadhukhan, ; Pathak & Shukla, ; Puppim de Oliveira & Doll, ; Woodcock et al, ). However, only few transport studies look at trade‐offs between GHG mitigation, land use, inclusivity and the local environment (Arora et al, ; Doll, Dreyfus, Ahmad, & Balaban, ; Li, ).…”
Section: Mainstreaming India's Urban Climate Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…An India‐wide study suggested that an increase in electricity consumption, modern cooking and clean water could lower short‐term morbidity for 2.4 million people with only modest increases to GHG emissions (Ahmad, Pachauri, & Creutzig, ). A range of studies point out that public and para transport can enhance safety, health and GHG mitigation (Ahmad et al, ; Arora et al, ; Doll & Balaban, ; Guttikunda, ; Maitra & Sadhukhan, ; Pathak & Shukla, ; Puppim de Oliveira & Doll, ; Woodcock et al, ). However, only few transport studies look at trade‐offs between GHG mitigation, land use, inclusivity and the local environment (Arora et al, ; Doll, Dreyfus, Ahmad, & Balaban, ; Li, ).…”
Section: Mainstreaming India's Urban Climate Responsesmentioning
confidence: 99%
“…In Delhi and Kolkata, studies proposed both affordable and low-carbon residences with end-use efficiency, rooftop solar and waste-to-energy plants (Colenbrander et al, 2016;Farzaneh, Suwa, Doll, & de Oliveira, 2014). In Surat, a waste-to-energy plant reduced carbon emissions and water pollution, accruing in local health benefits (Kapshe, Kuriakose, Srivastava, & Surjan, 2013;Puppim de Oliveira & Doll, 2016). Another analysis shows how existing actions on biodiversity, slum development, solid-waste management, water supply, energy, transport, housing and urban development can be further enhanced to achieve multiple benefits (Narender & Sethi, 2018).…”
Section: Mainstreaming India's Urban Climate Responsesmentioning
confidence: 99%
“…Potential to reduce energy consumption by 10-30% 45,46 Reduced travel times; public health, safety, and more equitable access 37,39,47,48 Shift Structure (shift to more energyefficient modes)…”
Section: Approachmentioning
confidence: 99%
“…The growing significance of urban areas is recognized by including Goal 11 (sustainable cities and communities) in the United Nations Sustainable Developmental Goals (SGDs). Cities are knowledge and innovation hubs, that can drive the urban system towards better governance of health and the climate within cities, and are centres which catalyse societal transformations (de Oliveira and Doll 2016). Most of the urban regions are located in coastal areas (Small and Nicholls 2003).…”
Section: Introductionmentioning
confidence: 99%